2014
DOI: 10.1016/j.bbamem.2013.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic analyses of integral membrane transport proteins encoded within the genome of the planctomycetes species, Rhodopirellula baltica

Abstract: Rhodopirellula baltica (R. baltica) is a Planctomycete, known to have intracellular membranes. Because of its unusual cell structure and ecological significance, we have conducted comprehensive analyses of its transmembrane transport proteins. The complete proteome of R. baltica was screened against the Transporter Classification Database (TCDB) to identify recognizable integral membrane transport proteins. 342 proteins were identified with a high degree of confidence, and these fell into several different cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 150 publications
1
8
0
Order By: Relevance
“…Indeed, horizontally acquired genes that have a useful function are maintained as it follows a strategy of colonization and adaptation to the environment. Our findings confirm previous results showing that HT particularly affects the genes involved in lipid metabolism, signal transduction and membrane transport in PVC bacteria, and genes specific to outer membrane (such as O-antigen polymerase and outer membrane efflux protein) in some Planctomycetes [ 43 , 86 , 87 ]. Since, the intracytoplasmic membrane of compartmentalized bacteria is a lipid bilayer, we can assume that the over-representation of the two functions in the genes transferred could be related to the cell plan of the bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, horizontally acquired genes that have a useful function are maintained as it follows a strategy of colonization and adaptation to the environment. Our findings confirm previous results showing that HT particularly affects the genes involved in lipid metabolism, signal transduction and membrane transport in PVC bacteria, and genes specific to outer membrane (such as O-antigen polymerase and outer membrane efflux protein) in some Planctomycetes [ 43 , 86 , 87 ]. Since, the intracytoplasmic membrane of compartmentalized bacteria is a lipid bilayer, we can assume that the over-representation of the two functions in the genes transferred could be related to the cell plan of the bacteria.…”
Section: Discussionsupporting
confidence: 91%
“…The proteinaceous exterior of G. obscuriglobus has not been shown to constitute a surface layer (S-layer), typically composed of only one or two proteins in a lattice configuration, like that found in some other bacteria, including archaea and the planctomycete "Candidatus Kuenenia stuttgartiensis" (13,22,23). The original cell wall analysis of G. obscuriglobus by Stackebrandt et al (18) found the cell wall composition to include many amino acids, and the ability of the G. obscuriglobus cell to maintain its integrity was demonstrated by the finding that cell sacculi retained their native cell morphology after 10% SDS treatment (18), thus exhibiting resistance to SDS that is more like that of cells that have a peptidoglycan-containing murein sacculus (21). Despite that resistance ability, the cell wall of G. obscuriglobus was actually found in that study not to contain muramic acid and diaminopimelic acid, which are considered peptidoglycan markers (18).…”
mentioning
confidence: 99%
“…The absence of peptidoglycan and presence of a proteinaceous cell wall (18) had long been distinguishing planctomycete features that led to the proposal of a unique cell plan for all planctomycetes (3,5,6,13,19). The proteinaceous barrier was previously suggested to substitute for other classical Gram-negative cell features, such as cell surface protection more typically provided by O antigen (20), a rigid structural framework in place of peptidoglycan (13), and possibly as an attachment platform for degradative enzymes, as in a related species, Rhodopirellula baltica (21). The proteinaceous exterior of G. obscuriglobus has not been shown to constitute a surface layer (S-layer), typically composed of only one or two proteins in a lattice configuration, like that found in some other bacteria, including archaea and the planctomycete "Candidatus Kuenenia stuttgartiensis" (13,22,23).…”
mentioning
confidence: 99%
“…The pie charts represent the relative abundances of relevant OTU sequences. The trees based on Jukes-Cantor distance was constructed using Mega 7.0 with a bootstrap value of 1000 would drive the enzyme-encoding sodium pumping NADH: quinone oxidoreductase (sodium-NQR) and Na + -ATPases to transport sodium ion into cell for smf generation, rather than proton motive force (Paparoditis et al 2014). Next, the enzyme-encoding Na + -translocating (RNF) is activated by the smf and pump Na + out with reduction of ferredoxin for carbon metabolism (de Almeida et al 2016).…”
Section: Discussionmentioning
confidence: 99%